Research anthology on changing dynamics of diversity and safety in the workforce (Business Science Reference, 2021)
"This publication of contributed chapters provides the latest emerging research on diversity management and initiatives as well as occupational health and safety practices in the workplace to ensure the global workplaces remain safe, efficient, and inclusive"--